The politics of irony, reconsidered. Issue 2 (3rd April 2021) - Grimwood, Tom
ABSTRACT: Franco 'Bifo' Berardi concludes his analysis of critical malaise in late capitalism with a bold call to arms: post-liberal dystopia must be faced and dissolved by irony. He argues for a renewed ironic autonomy, which emphasises the independence of mind from knowledge and the excessive nature of the imagination. Developing Berardi's argument, I suggest there are three obstacles to theorising irony as a form of politics. The first is that a politics of irony is often accused of being either a fraudulent or amoral form of politics, which has itself allowed a post-liberal malaise to fester and grow. The second problem is that irony may no longer be simply an ambivalent tool of critique from the edges of political discourse, but instead a tool which perpetuates its very centre. The third problem is that theorising the performance and place of irony in relation to political critique often results in a slippage from the complexity of the second problem to the impasse of the first. I argue that Berardi's 'ironic autonomy' is entirely possible, so long as the politics of irony is understood as depending on the different forms and media of interpretative space through which contemporary politics takes place.